Platinum‐Tin/Tin Oxide/CNT Catalysts for High‐Performance Electrocatalytic Ethanol Oxidation. Issue 4 (8th December 2021) - Zheng, Zhiping; Jiang, Qiaorong; Cheng, Xiqing; Han, Xiao; Kuang, Qin; Xie, Zhaoxiong
Abstract: Ethanol is a promising liquid clean energy source in the energy conversion field. However, the self‐poisoning caused by the strongly adsorbed reaction intermediates (typically, CO) is a critical problem in ethanol oxidation reaction. To address this issue, we proposed a joint use of two strategies, alloying of Pt with other metals and building Pt/metal‐oxide interfaces, to achieve high‐performance electrocatalytic ethanol oxidation. For this, a well‐designed synthetic route combining wet impregnation with a two‐step thermal treatment process was established to construct PtSn/SnOx interfaces on carbon nanotubes. Using this route, the alloying of Pt−Sn and formation of PtSn−SnOx interfaces can simultaneously be achieved, and the coverage of SnOx thin films on PtSn alloy nanoparticles can be facilely tuned by the strong interaction between Pt and SnOx . The results revealed that the partial coverage of SnOx species not only retained the active sites, but also enhanced the CO anti‐poisoning ability of the catalyst. Consequently, the H−PtSn/SnOx /CNT‐2 catalyst with an optimized PtSn−SnOx interface showed significantly improved performances toward the ethanol oxidation reaction (825 mA mgPt −1 ). This study provides deep insights into the structure‐performance relationship of PtSn/metal oxide composite catalysts, which would be helpful for the future design and fabrication of high‐performance Pt‐based ethanol oxidation reaction catalysts. Abstract : The interfacial structure of Pt−Sn/SnOx /CNT composite electrocatalysts was rationally engineered on carbon nanotubes for achieving high‐performance electrocatalytic ethanol oxidation. Through a carefully designed two‐step (oxidation‐reduction) heat‐treatment route, the coverage of SnOx thin films on PtSn alloy nanoparticles can be facilely tuned by the strong interaction between Pt and SnOx . The optimized PtSn−SnOx interface showed significantly improved performances toward ethanol oxidation reaction.